Klimat organizacyjny jako jeden z zasobów w procesie radzenia sobie ze stresem – badania porównawcze pracowników polskich i niemieckich firm - Świętochowski, Waldemar (Acta Universitatis Lodziensis. Folia Psychologica, 2007)
Presented paper deals with the dependency between organisational interpersonal atmosphere in organisations and coping strategies, used by polish and german workers. There were 30 Polish and 30 German subjects, representing three kinds of business companies: commercial, concerning computer technology and productive. The methods were Kolb’s Questionnaire for Organisational Atmosphere and Coping Inventory of Stress Strategy by Endler and Parker, both in Polish or German linguistic version. The results suggest that there is certain difference between Polish and German workers: the former are used to apply coping strategies, which are appropriate to the perceived organisational weaknesses, the latter – mostly use strategies directed towards the emotional discomfort and tension. Surprisingly, the Poles who are functioning in well organised office are motivated to use mainly emotional (and avoiding) strategies, what may be understood as a result of weak identification with the organisation.